The Internationalization of Boot Camp - Sveinbjörg Rut Pétursdóttir 1981- (2011)
Boot Camp’s history and structure is explored as well as the Icelandic and Danish market. The thesis explores theories of internationalization, different forms of entry modes, and competitive resources in the case of Boot Camp. Boot Camp has recently started its pathway of internationalization but no other Icelandic fitness company to the researcher’s knowledge has successfully managed to internationalize. The international name of Boot Camp was changed to Budz Boot Camp when they started the internationalization process. There may be different motives behind a company’s internationalization and different theories for choosing which market to enter. The theoretical chapter gives an overview of different theories of internationalization and entry modes which were thought to be appropriate to the case of Boot Camp, as well as exploring in-depth the resource-based view which is the main theoretical base for the analysis. Internationalization theories vary between countries and evolve through the company’s experience. Findings of this research include that there seem to be consumer similarities in Iceland and Denmark and the competitive advantages identified are similar for Boot Camp in Iceland and Budz Boot Camp in Denmark. The main conclusion is that internationalization is a viable option for Boot Camp. The concept of Boot Camp is a niche differentiation which is also one of the characteristics identified in Óladóttir’s (2009) research about internationalization of Icelandic companies. If those resources that provide competitive advantage are not fully exploited it could lead to a failure of the operation.